2022
DOI: 10.1108/sbm-06-2021-0067
|View full text |Cite
|
Sign up to set email alerts
|

The impact of environmental barriers on attendance of outdoor and indoor professional sports: the case of the South Korean soccer, baseball and basketball leagues

Abstract: PurposeThis study sought to determine if environmental barriers (i.e. air pollution, temperature and precipitation) affect outdoor (i.e. soccer and baseball) and indoor (i.e. basketball) professional sport attendance in South Korea.Design/methodology/approachBy including actual air quality, temperature and precipitation data collected from each place where the sporting events take place, this study conducted a regression analysis to examine factors that influenced outdoor and indoor sport attendance.FindingsIn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 79 publications
(184 reference statements)
0
2
0
Order By: Relevance
“… Mulville et al (2016) investigated the relationship between ambient environment and productivity in open-plan commercial offices and recommended that ambient environments significantly affect the health, comfort, and wellbeing which eventually influence the productivity of the workers. Another study on creative and productive workplaces concluded that environmental elements significantly affect the employee’s wellbeing which eventually influences their effectiveness and performance ( Clements-Croome, 2015 ; Lee et al, 2022 ). It is an enormous reality that a poor environment contributes to absenteeism and workers cannot work well.…”
Section: Literature Reviewmentioning
confidence: 99%
“… Mulville et al (2016) investigated the relationship between ambient environment and productivity in open-plan commercial offices and recommended that ambient environments significantly affect the health, comfort, and wellbeing which eventually influence the productivity of the workers. Another study on creative and productive workplaces concluded that environmental elements significantly affect the employee’s wellbeing which eventually influences their effectiveness and performance ( Clements-Croome, 2015 ; Lee et al, 2022 ). It is an enormous reality that a poor environment contributes to absenteeism and workers cannot work well.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Nevertheless, the impacts of outdoor air quality, specifically in areas with greater air pollution, remain a largely understudied area of concern for athlete performance and overall health. Although declining air quality has not significantly discouraged fan attendance at elite athletic events [29,30], there appears to be adverse impacts on athletes when competing in areas with poorer outdoor air quality, as indicated by reductions in high-intensity performance [31]. These studies, in combination with others that have directly shown causative declines in physical health (e.g., [6,7,16,17]), collectively indicate that air quality has impacts on athletic performance, specifically on athletes competing at elite levels where minute differences in physical capacity can determine the outcome of a competition.…”
Section: Introductionmentioning
confidence: 99%